Gastric Cancer Imaging: Computed Tomographic Pneumogastrography - I. D. Amelina; L. N. Shevkunov; A. M. Karachun; A. L. Muravtseva; A. S. Artemyeva (Вестник рентгенологии и радиологии)
Objective: to reveal technical nuances for obtaining high-quality images using a computed tomography protocol with pneumogastrography and virtual gastroscopy, which contribute to the detection and assessment of the morphological type of gastric cancer and to the determination of its localization and invasion depth.Material and methods. The investigation enrolled 250 patients with both early (24.8%) and locally advanced (75.2%) gastric cancer treated in Petrov National Medical Research Center for Oncology from 2015 to 2018. Preoperative chemotherapy was performed in 142 (56.8%) patients and was not done in 108 (43.2%). All the patients underwent preoperative computed tomography with pneumogastrography and virtual gastroscopy. All the patients were radically operated on through subtotal or total gastric resection.Results. Computed tomography with pneumogastrography and virtual gastroscopy was used to detect gastric cancer in 98.4% of patients; the cases with early T1a and T1b invasion depth cancers were 23.2%. The tumor could not be significantly differentiated in 4 (1.6%) patients. This group consisted of: 3 (1.2%) and 1 (0.4%) patients with pT1a and pT1b invasion depth tumors, respectively. All non-visualized tumors had a superficial morphological type of growth (Type 0–II (3 cases with 0–IIa and 1 case with 0–IIb); their sizes were less than 2 cm. Three tumors were localized in the antral portion of the stomach; one was in its cardiac portion.Conclusion. Computed tomography with pneumogastrography and virtual gastroscopy is an effective technique to detect gastric cancer, including its early types of category T1, which makes it possible to assess its localization, morphological type, and invasion depth.